2021
DOI: 10.1002/pd.6022
|View full text |Cite
|
Sign up to set email alerts
|

Utility of fetal whole exome sequencing in the etiological evaluation and outcome of nonimmune hydrops fetalis

Abstract: Introduction Nonimmune hydrops fetalis (NIHF) has varied etiology. We assessed the etiological spectrum and evaluated the utility of fetal whole exome sequencing (fWES) for the diagnosis of NIHF. Methods In this prospective cohort study, we evaluated antenatally diagnosed fetuses with NIHF between July 2018 and December 2019 according to the routine diagnostic algorithm. Fetuses that remained undiagnosed after routine NIHF workup were subjected to fetal chromosomal microarray and/or WES. Pregnancies were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“… 32 , 41‐48 , 33‐40 Eight studies targeted ES analysis more tightly using phenotype‐specific gene panels, 7 , 12 , 15 , 49‐53 while the remainder took a whole ES approach 8 ,. 13 , 62‐71 , 54 , 72‐81 , 55 , 82‐88 , 56‐61 Where stated (15 studies), 7 , 8 , 74 , 75 , 78 , 82 , 84 , 15 , 29 , 36 , 52 , 53 , 55 , 62 , 73 the median turnaround time for ES was 20 days (range 4–141). Studies included fetuses with a range of structural abnormality phenotypes, with some studies recruiting cases with fetal anomalies in a specific body system (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 , 41‐48 , 33‐40 Eight studies targeted ES analysis more tightly using phenotype‐specific gene panels, 7 , 12 , 15 , 49‐53 while the remainder took a whole ES approach 8 ,. 13 , 62‐71 , 54 , 72‐81 , 55 , 82‐88 , 56‐61 Where stated (15 studies), 7 , 8 , 74 , 75 , 78 , 82 , 84 , 15 , 29 , 36 , 52 , 53 , 55 , 62 , 73 the median turnaround time for ES was 20 days (range 4–141). Studies included fetuses with a range of structural abnormality phenotypes, with some studies recruiting cases with fetal anomalies in a specific body system (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…14,32,[41][42][43][44][45][46][47][48][33][34][35][36][37][38][39][40] Eight studies targeted ES analysis more tightly using phenotypespecific gene panels, 7,12,15,[49][50][51][52][53] while the remainder took a whole ES approach. 8,13,[62][63][64][65][66][67][68][69][70][71]54,[72][73][74][75][76][77][78][79][80][81]55,[82][83]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Recent studies already showed the advantage of further genetic follow-up using exome sequencing. These investigations showed diagnostic yields of exome sequencing in fetal hydrops between 29 and 42.1% [20][21][22], suggesting that exome sequencing will play an increasing role in the clinical workup of NIFH.…”
Section: Discussionmentioning
confidence: 93%
“…The 45% surviving the neonatal period demonstrated highly variable clinical presentation, ranging from complete resolution of the hydrops with childhood recurrence of lymphedema, to severe neonatal condition and recurrent cellulitis requiring prolonged intensive care, but with normal intelligence. Recent studies about ES for diagnosis in non-immune hydrops fetalis have found about 0.8 to 7% (1/127 and 2/28) of LMPHM6 with autosomal recessive variants in PIEZO1 (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now about 32 LoF variants in PIEZO1 have been reported in 18 GLD families (7)(8)(9)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The affected individuals exhibit highly variable clinical presentation, ranging from mild lymphedema of childhood onset to severe NIHF with intrauterine fetal demise or neonatal demise.…”
Section: Introductionmentioning
confidence: 99%